2009
DOI: 10.1002/hec.1465
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rural mutual health care on health status: evaluation of a social experiment in rural China

Abstract: Despite widespread efforts to expand health insurance in developing countries, there is scant evidence as to whether doing so actually improves people's health. This paper aims to fill this gap by evaluating the impact of Rural Mutual Health Care (RMHC), a community-based health insurance scheme, on enrollees' health outcomes. RMHC is a social experiment that was conducted in one of China's western provinces from 2003 to 2006. The RMHC experiment adopted a pre-post treatment-control study design. This study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 36 publications
2
79
0
Order By: Relevance
“…Wang et al (2009) do find some positive effects of health insurance coverage on self-reported health status, but the insurance program they studied is different from the NCMS and arguably more comprehensive in outpatient care and could offer more help to deal with non-catastrophic health risk. Since our studied area is much poorer than most areas of China, we suspect that the NCMS does not improve the three studied outcomes in other areas either.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Wang et al (2009) do find some positive effects of health insurance coverage on self-reported health status, but the insurance program they studied is different from the NCMS and arguably more comprehensive in outpatient care and could offer more help to deal with non-catastrophic health risk. Since our studied area is much poorer than most areas of China, we suspect that the NCMS does not improve the three studied outcomes in other areas either.…”
Section: Discussionmentioning
confidence: 89%
“…More specifically, Wang et al (2009) and Wagstaff et al (2009) propose estimators similar to ATE P-NE . 19 This is still biased because insurance participants are a selected group and the distribution of Z ip could be systematically different from Z i NE even if the two sets of counties are overall comparable.…”
Section: Our Methodology: Did In Propensity Score Matchingmentioning
confidence: 97%
“…Barros found, as we did, a substitution of visits to service providers and a reduction in out of pocket expenditures. See also Wang et al (2009). Other studies have evaluated the effects of health insurance in Columbia and have also found increased utilization and reduced out-of pocket expenditure (Giedion et al, 2007).…”
Section: Background and Program Descriptionmentioning
confidence: 99%
“…2 (August 2013) Mensah et al (2010) show lower levels of infant death, although these levels are not statistically significant. Wang et al (2009) use EQ-5D, a standardized index value instrument for use as a measure of a wide range of health conditions, to report on a community-based health insurance program in China. They find that the scheme had positive effects on health status for all insured people and for the poor.…”
mentioning
confidence: 99%